PERANCANGAN MODEL BISNIS MENGGUNAKAN PENDEKATAN BUSINESS MODEL CANVAS UNTUK MENGEMBANGKAN USAHA KECIL MENENGAH - Muhammad Tahwin; Agus Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This research aim is to formulate business model for developing Batik Tulis Lasem Industry. The research object is Batik Tulis Lasem industry in Rembang Regency. The collecting data used is questioner and interview. The sample is 42 Batik Tulis Lasem entrepreneurs taken by purposive sampling. Analyzing data used is descriptive analysis technique, SWOT analysis and Business Model Canvas Approach. The result of the research shows that business model developed is Business Model Canvas by considering Existing condition. Some segment blocks must be developed and created. Customer segment block is the customers’ segment based on the area developed. Motif and design patent proposed have to be developed in value propositions block, and creating interesting design, motif and the packaging. The use of Dekranasda Showroom has to be improved in channels block and created the outside area promotion, e-marketplace and online selling. In costumer relationship block must be improved the services qualities and created customers’ fulfillment and loyalty. In revenue stream block must be developed and created the existing currents from product variation. In key resources block must be improved the labor skill. Key block activities must be carried out to improve capacity and quality of human resources. Key partnership is the existing condition improved and networking created for the same field entrepreneurs. Cost structure is the existing condition survived